The Effect of Organizational Commitment and Placement on Employee Performance at The Regional Financial Management Agency (BPKD) of Bengkulu Province - Agusman Ameri; Ida Anggriani; Tito Irwanto (Penerbit Jurnal Indonesia, 2021)
The purpose of this study is to determine the effect of organizational commitment and placement on employee performance at the Regional Financial Management Agency (BPKD) of Bengkulu Province. The sample in this study was 46 civil servants at the Regional Financial Management Agency (BPKD) of Bengkulu Province. The data were collected using a questionnaire and the analytical method used was multiple linear regression, determination test and hypothesis testing. The results of the regression analysis show Y = 7,828 +0,386X1 +0,445 X2, this describes a positive regression direction, meaning that there is a positive influence between X1 (organizational commitment) and X2 (placement) on performance (Y). It means that if the variable of organizational commitment and placement increases, it will increase performance. The value of the coefficient of determination is 0.557. This means that X1 (organizational commitment) and X2 (placement) affect performance (Y) by 55.7% while the remaining 44.3% is influenced by other variables not examined in this study. 0.05 explains that partially organizational commitment and placement variables have a significant influence on employee performance variables at the Bengkulu Province Regional Financial Management Agency (BPKD). The F test results at a significance level of 0.05 explain that organizational commitment and placement variables have a significant effect significant simultaneous effect on employee performance at the Regional Financial Management Agency (BPKD) of Bengkulu Province.